2020
DOI: 10.21831/jpji.v16i1.29639
|View full text |Cite
|
Sign up to set email alerts
|

Kompetensi guru pendidikan jasmani olahraga dan kesehatan ditinjau dari usia dan jenis sekolah

Abstract: Kompetensi pedagogik dan profesional sebagian guru pendidikan jasmani, olahraga, dan kesehatan (PJOK) ditengarai lemah, terutama pada guru berusia lanjut. Hal ini ditandai dengan adanya data guru PJOK berusia lanjut kesulitan mengikuti perubahan kurikulum, menyusun RPP dengan sistematika lama, melaksanakan pembelajaran dengan cara lama, dan tetap mengajarkan teknik-teknik dasar kecabangan olahraga. Penelitian ini bertujuan untuk mengetahui hubungan kompetensi pedagogi dan kompetensi professional guru PJOK deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
5
0
3
Order By: Relevance
“…However, blended learning approach and balanced with proficiency in the use of technology, teachers get an improvement in the quality of learning with a variety of information through various social media platforms (Winarni & Lismadiana, 2020;Sujarwo & Rachman, 2020). The use of technology in the modern era in physical education learning and combined with blended learning models, can increase students' understanding cognitively and psychomotorly (Sabillah & Nasrulloh, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, blended learning approach and balanced with proficiency in the use of technology, teachers get an improvement in the quality of learning with a variety of information through various social media platforms (Winarni & Lismadiana, 2020;Sujarwo & Rachman, 2020). The use of technology in the modern era in physical education learning and combined with blended learning models, can increase students' understanding cognitively and psychomotorly (Sabillah & Nasrulloh, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of length of service states that there is a significant influence between size of service and level of competency, so it can be concluded that the higher the length of service, the lower the level of teacher competency (Prasetyo et al, 2020). The teacher's experience will significantly influence their ability to carry out their duties and increase teacher competence (Winarni & Lismadiana, 2020). For teachers who have only a few years of teaching experience or no experience at all, it will be different from teachers who have had many years of teaching experience.…”
Section: Differences In the Implementation Of Pe Learning Planning Co...mentioning
confidence: 99%
“…Then, several researchers such as Rahman [29] and Kumala [30]8 show that there are differences in teacher competence in public schools and private schools. Nevertheless, there are other researchers such as Sopiana, 2016; Winarni & Lismadiana [31], and Damayanti [32] which show that there are differences in teacher competence in public and private schools.…”
Section: Introductionmentioning
confidence: 99%